Respuesta :
A. (x+8)² is the correct answer.
First, you had to break the expression into their groups.
And it gave us ⇒ [tex](x^2+8x)+(8x+64)[/tex]
Then, you had to factor it out from x²+8x=x(x+8).
Next, factor you had to factor it out from 8x+64=8(x+8)
And it gave us ⇒ [tex]x(x+8)+8(x+8)[/tex]
You can also keep the factor of their common term of (x+8).
And it gave us ⇒ [tex](x+8)(x+8)[/tex]
Finally you had to refine and it gave us the final answer is.
And it gave us ⇒ [tex](x+8)^2[/tex]
Hope this helps! And thank you for posting your question at here on brainly, and have a great day. -Charlie
Answer: I got it correct on the test :D
Step-by-step explanation:
![Ver imagen goobermonkey3312](https://us-static.z-dn.net/files/d9b/16e92cc841750bcf6618d492321acd24.png)